2018
DOI: 10.31386/dmj.2017.11.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Annual Incidence of Congenital Hypothyroidism in Sulaimani City-Kurdistan Region/Iraq

Abstract: Background: Congenital hypothyroidism is one of the most common preventable causes of intellectual disability. Most neonates born with congenital hypothyroidism are normal on clinical examination. Hypothyroidism in the newborn period is almost always overlooked, and as a result delay in management will cause profound neurological insult and mental retardation. Neonatal screening in Sulaimani city (center of Sulaimani governorate in north of Iraq) had started in 2013 for screening of Phenylketonuria, congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…The present study's findings contradicted those from Australia and Nepal, which revealed rates of 18.6 percent and 22.42 percent, respectively. (Merno-asso et al, 2020;Sharma, Magar, & Mahesh, 2021) while it was in agreement with 14.45 % and 14.6 % that recorded in Baghdad and Sulaimania in Iraq respectively also (Faisal, 2010;HASAN, SAEED, RASHID, & ABDULLAH, 2017). Although the prevalence of local thyroid dysfunction was 14.81 percent in urban regions compared to 12.5 percent in rural areas, the rate of hyperthyroidism was 9.87 percent higher in rural areas than in urban areas, where the rate was 4.93 percent.…”
Section: Discussionsupporting
confidence: 83%
“…The present study's findings contradicted those from Australia and Nepal, which revealed rates of 18.6 percent and 22.42 percent, respectively. (Merno-asso et al, 2020;Sharma, Magar, & Mahesh, 2021) while it was in agreement with 14.45 % and 14.6 % that recorded in Baghdad and Sulaimania in Iraq respectively also (Faisal, 2010;HASAN, SAEED, RASHID, & ABDULLAH, 2017). Although the prevalence of local thyroid dysfunction was 14.81 percent in urban regions compared to 12.5 percent in rural areas, the rate of hyperthyroidism was 9.87 percent higher in rural areas than in urban areas, where the rate was 4.93 percent.…”
Section: Discussionsupporting
confidence: 83%